Evidence of Fear in Fixed Income and Bourses: A Study on Certain G-7 Economies - Janardan, Shriya (Ushus Journal of Business Management, 2019)
The paper aimed to predict the Fear index for certain G7 countries (Canada, France, Germany and Japan) considering the two variables Stock Price (Close) and Bond Yield(LBY). Daily data were analyzed for the period from April 2013 to June 2017. The main purpose was to identify the degree in which fear affecting the stock market percolates to Fixed Income Instruments. Using Panel Data Regression (Fixed Effect Model) the two variables were able to predict the VIX index and the model was found to be robust in nature. The major finding is that Fixed Income and stocks share a negative relationship with VIX (Fear Index).